PENGARUH SUPERVISI KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SDN 1 RANTEPAO - Eden Gloria Simon Tato; Witarsa Tambunan; T Sunaryo (Jurnal Manajemen Pendidikan, 2022)
The problems discussed in this study are the Effect of Principal Supervision and Work Motivation on Teacher Performance at SDN 1 Rantepao. This study aims to analyze (1) the effect of principal supervision on teacher performance at SDN 1 Rantepao, (2) the effect of work motivation on teacher performance at SDN 1 Rantepao, (3) the effect of principal supervision and work motivation on teacher performance at SDN 1 Rantepao. The method used in this study is a quantitative method with a survey research approach. The results showed that: (1) there was a positive and significant effect of Principal Supervision on teacher performance, which obtained tcount = 3.050 then significant 0.006 <0.05, while the contribution given was 25.4%, H0 was rejected and H1 was accepted, (2) there was an influence positive and significant work motivation on teacher performance. This can be seen from the results of data analysis where tcount = 7.015 is obtained and the significance is 0.000 <0.05, while the contribution given is 70.6%, H0 is rejected and H1 is accepted, (3) there is an influence of Principal Supervision and work motivation on teacher performance of 86.8% and significant together. This can be seen from the results of data analysis, the results of Fcount > Ftable with Fcount of 8.488 and Ftable of 3.16 then H0 is rejected and H1 is accepted.